2015
DOI: 10.1016/j.gpb.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Autoantigen Microarray for High-Throughput Autoantibody Profiling in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a complex autoimmune disease characterized by the production of autoantibodies to a broad range of self-antigens. Profiling the autoantibody repertoire using array-based technology has emerged as a powerful tool for the identification of biomarkers in SLE and other autoimmune diseases. Proteomic microarray has the capacity to hold large number of self-antigens on a solid surface and serve as a high-throughput screening method for the determination of autoantibody specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 55 publications
1
79
0
Order By: Relevance
“…They concluded that complement C3 binding to nucleic acid serves as immunogenic target in lupus and act as a prognostic marker in murine model of SLE. A more in-depth analysis of the applications of microarray for the Aab detection in SLE has been discussed by Zhu et al [31]. Rheumatoid arthritis is another common autoimmune disorder where the body attacks its own cartilage and bones, which results in chronic joint inflammation deteriorating to irreversible joint destruction.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…They concluded that complement C3 binding to nucleic acid serves as immunogenic target in lupus and act as a prognostic marker in murine model of SLE. A more in-depth analysis of the applications of microarray for the Aab detection in SLE has been discussed by Zhu et al [31]. Rheumatoid arthritis is another common autoimmune disorder where the body attacks its own cartilage and bones, which results in chronic joint inflammation deteriorating to irreversible joint destruction.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…Moreover, detection of PTMs can be incorporated in microarray screening by using synthetic platforms such as a glycosylated peptide array (77). An additional benefit of this technology includes profiling autoantibody signatures during disease progression (78), as has been shown in a recent review describing the use of proteomic microarrays to study autoantibody profiles in systemic lupus erythematosus (79).…”
Section: Array-based Immunoscreening Technologiesmentioning
confidence: 99%
“…As one example of this variety relevant to this discussion, there are at least 180 autoantibody targets identified for SLE [118,119]. Many of these do not appear to have any clear relation to the others.…”
Section: Discerning Patterns Among Autoantigens In Adsmentioning
confidence: 99%